Harnessing Gemini for Arabic Mastery: Educators' and Learners' Views - Zaimah, Nely Rahmawati; Risti Kamila Wening Estu; Hidayah, Syarifatul Fitri; Hadi, Syamsul; Aiden Button (IAIN Madura, 2024)
This study aims to explore the perspectives on the reliability of Gemini in Arabic language studies, supported by a comprehensive literature review for each segment. Adopting a qualitative phenomenological approach, the research focuses on examining the experiences and perceptions of academics regarding the use of the Gemini chatbot. The research population includes 120 students studying Quranic Sciences and Exegesis at STAI Al-Anwar Rembang, purposefully selected for their collective proficiency in the Arabic language. Additionally, 11 Arabic language teachers in Rembang are actively involved in developing a structured teaching framework enriched by Gemini. The result highlights the importance of collaboration among linguists, educators, and tech developers in leveraging Gemini, an AI tool, for effective Arabic language education, while addressing accuracy and privacy concerns. The researcher anticipates that this study will provide insights into integrating AI tools like Gemini into Indonesian curricula, enhancing Arabic language learning. It seeks to contribute to the discourse on technology-enhanced language education and its practical implications.